Cell Cycle Control and Dysregulation Protocols - Giordano, Antonio; Romano, Gaetano; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
The dysregulation of the normal cell cycle underlies an enormous number of pathological conditions, including the neurodegenerative disorders, all cancers, and diabetes. In Cell Cycle Control and Dysregulation Protocols: Cyclins, Cyclin-Dependent Kinases, and Other Factors, expert laboratorians detail emerging methodologies for studying the cell cycle, its kinases, and kinase inhibitors. The authors focus on issues of gene expression in vivo and in vitro, the analysis of cyclin-dependent kinase inhibitors, protein degradation mediated by the proteosome, the analysis of the transformed cell phenotype, and innovative techniques to detect apoptosis. Many of the protocols are new, such as electron microsocopy to detect apoptosis and proteosome-mediated degradation, whereas others study the interactions between protein-protein, protein-DNA, and protein-RNA. The protocols follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. State-of-the-art and highly practical, Cell Cycle Control and Dysregulation Protocols: Cyclins, Cyclin-Dependent Kinases, and Other Factors offers pathbreaking researchers powerful tools for probing the cell cycle regulation across a wide variety of pathologies.
Analysis of Cyclins and Cyclin-Dependent Kinases -- The Biology of Cyclins and Cyclin-Dependent Protein Kinases -- In Situ Immunofluorescence Analysis -- In Situ Immunofluorescence Analysis -- Immunofluorescence Analysis Using Epitope-Tagged Proteins -- Analysis of In Vivo Gene Expression Using Epitope-Tagged Proteins -- Chromatin Immunoprecipitation -- Protein-Deoxyribonucleic Acid Interactions Linked to Gene Expression -- Protein-Deoxyribonucleic Acid Interactions Linked to Gene Expression -- Protein-Deoxyribonucleic Acid Interactions Linked to Gene Expression -- Assays for Cyclin-Dependent Kinase Inhibitors -- Protein Degradation Via the Proteosome -- Analysis of the Factors Involved in Cell Cycle Deregulation -- The Transformed Phenotype -- A Morphologic Approach to Detect Apoptosis Based on Electron Microscopy -- Detection of Apoptotic Deoxyribonucleic Acid Break by In Situ Nick Translation -- Cellular Response to Deoxyribonucleic Acid Damage -- Induction of Deoxyribonucleic Acid Damage by Alkylating Agents -- Induction of Deoxyribonucleic Acid Damage by ? Irradiation -- Ultraviolet Irradiation of Cells -- Retroviridae-Based Vectors: Protocols for Lentiviral- and Retroviral-Mediated Gene Transfer to Engineer Cell Culture Systems -- Transient Production of Retroviral- and Lentiviral-Based Vectors for the Transduction of Mammalian Cells -- Determination of Functional Viral Titer by Drug-Resistance Colony Assay, Expression of Green Fluorescent Protein, and ?-Galactoside Staining -- Retroviral and Lentiviral Vector Titration by the Analysis of the Activity of Viral Reverse Transcriptase -- Detection of Gene Expression in Subcellular Compartments -- Single and Double Colloidal Gold Labeling in Postembedding Immunoelectron Microscopy -- Multifluorescence Labeling and Colocalization Analyses.
Keywords: Immunology; Immunology